"EXPRESSION OF SOCIAL REALITY IN ARTISTIC AND JOURNALISTIC WORKS OF ISHAQ KHAN TORA IBRAT" - Nasibakhan Mamatjanova (Scholar Express Journal, 2024)
In this article, Ishaq Khan Ibrat's work "History of Fergana", articles he gave to "Oyna" magazine, "Turkistan region's gazette", characteristics of views such as the attitude of khans and begs to historical events, place names, their definition, The events of the construction of the Kokon-Namangan railway are covered. Also, the work contains conclusions and suggestions on how to convey to the future generation about the way of life, culture and life of our ancestors, and to encourage them to draw conclusions from it
Keywords: Works of Ishaq Khan Ibrat; History of Fergana; Oyna